Coronary revascularization (Examples from the world and Turkey) - Yücel Balbay; Selim Bener; Taner Kaygusuz; Serkan Çay; Erdoğan İlkay (KARE Publishing, 2014)
Objectives: In this article, our aims were to analyze and assess the data related to coronary revascularization rates, particularly in recent years. Study design: For this purpose, results of important studies, statistics of the Organisation for Economic Co-operation and Development (OECD) countries and data from Turkey's Social Security Agency (SSA) were analyzed for the first time. Until recently, there has been no healthy digital database regarding revascularization rates in Turkey. In the years following the establishment of SSA, it became possible to collect and analyze data obtained from the Medulla database of the Agency. Using the data from the Agency for the period 2009-2011, revascularization rates and cost analyses were performed. Results: Between 2000 and 2010 in European countries as well as in other OECD countries, the percutaneous coronary intervention (PCI) rate was on average 75% of the total revascularization rate and neared 80%. In some countries, the rate has exceeded 85%. In our country, in 2009, 2010 and 2011, the number of coronary angiography procedures and as a result PCI has steadily increased. The rate for PCI was 66.8% in 2009, but it increased to 74% in 2011. At the same time, PCI accounted for 2/3-4/5 of all revascularization procedures. In the cost analysis, however, PCI constituted only 1/5-1/4 of the costs of all revascularization procedures. Conclusion: This report is the first analysis in this area and it gives an initial idea about the current situation of the numerical and financial aspects. This analysis has provided the opportunity to obtain more accurate information about coronary revascularization rates in Turkey and to compare the data to that of other countries.